Ensoulment and the prohibition of abortion in Islam - Hussain, Arif Abdul (Islam and Christian-Muslim relations, 2005)
This article identifies ways in which philosophical ideas of personhood influence rulings concerning abortion. The terms ‘life’, ‘soul’ and ‘spirit’ are clarified through a comparative study of authoritative Shi&art10;a texts. There is a consensus that ensoulment occurs at four months, when the spirit causes the emergence of potentiality for rational thought. This stage marks a significant change in the status of the foetus, and abortion after this stage is prohibited except in extreme circumstances when the mother's life is threatened. Recent rulings by Shi&art10;a scholars on abortion at earlier stages are interpreted in terms of potentiality for ensoulment. The distinction between active and passive potentiality for ensoulment clarifies the reasons why jurists hold different views on whether the prohibition of abortion applies before the stage of implantation. The relevance of this discussion to some methods of contraception is indicated.